Integrasi Moderasi Beragama dalam Pengembangan Kurikulum Pendidikan Agama Islam - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2020)
AbstractIn the midst of the strengthening of the discourse on character education, religious moderation, and countering religious radicalism and terrorism, the study of Islamic religious education in public schools based on Islamic boarding schools is interesting to do. In this context, various problems arise related to the material and content of the Islamic religious education curriculum (PAI). Education under pesantren is no longer directed at the mastery of religious knowledge but also general science. This of course has an impact on shifting curriculum content and its implementation. This study uses a descriptive qualitative approach based on empirical phenomena. Data were collected through interviews, involved observations, questionnaires, documentation, and literature review. This research produces a model for implementing religious moderation education through the development of the PAI curriculum to present a moderate Islamic movement among students that teaches: (1) building tolerance among different groups of students, both outside Islam and within Islam; (2) spreading peace in their social environment; (3) prioritizing interfaith dialogue and (4) instilling openness with outside parties and 4) rejecting hate speech (hoaxes) both inside and outside schools. This study recommends the importance of teaching and practicing religious moderation among students to present moderate Islamic movements and habituation of noble morals.Â AbstrakDi tengah menguatnya wacana pendidikan karakter, moderasi beragama, serta penanggulangan radikalisme dan terorisme bernunsa agama, kajian pendidikan agama Islam di sekolah umum berbasis pondok pesantren menarik untuk dilakukan. Dalam konteks ini muncul berbagai masalah terkait dengan materi dan muatan kurikulum pendidikan agama Islam (PAI). Pendidikan di bawah pesantren tidak lagi diarahkan pada penguasaan ilmu agama saja melainkan juga ilmu umum, Hal ini tentu berdampak pada pergeseran muatan kurikulum dan implementasinya. Penelitian ini menggunakan pendekatan kualitatif deskritif berdasarkan fenomena empirik. Data dikumpulkan melalui wawancara, pengamatan terlibat, angket, dokumentasi, dan kajian pustaka. Penelitian ini menghasilkan model penyelenggaraan pendidikan moderasi beragama melalui pengembangan kurikulum PAI untuk menghadirkan gerakan Islam moderat di kalangan peserta didik yang mengajarkan: (1) membangun toleransi di antara kelompok peserta didik yang berbeda, baik di luar Islam maupun di dalam Islam; (2) menebarkan perdamaian di lingkungan sosialnya; (3) mengedepankan dialog antar agama dan (4) menanamkan sikap keterbukaan dengan fihak luar dan 4) menolak ujaran kebencian (hoax) baik didalam dan luar sekolah. Penelitian ini merekomendasikan pentingnya mengajarkan dan mengamalkan moderasi beragama di kalangan peserta didik untuk menghadirkan gerakan Islam moderat dan pembiasaan berakhlak mulia.